Evaluation of the use of distance and remote education at Federal Institutes high school in the southeast region before and during Covid-19 pandemic (Research, Society and Development, 2020)
Distance education (DE) has advantages such accessing information flexible, and skills development. Covid-19 pandemic and the suspension of face-to-face classes resulted in adoption of remote education (RE) by schools, and universities similar to DE, but without same planning. The objective of this study was to investigate the use of DE and RE in Federal Institutes (FIs) high schools in the Southeast Region, before, during, and after Covid-19 pandemic. For this purpose we created objective questions at the Google Forms and sent by email for 141 FIs in the Southeast Region. We found that DE was few adopted in high school (17.8%), and that RE was adopted in 97.8% of the FIs studied, frequently use of Moodle platform (52.2%). We analyzed that 76.1% of the teachers had not prior digital platforms knowledge, but was offered training during the pandemic in 91.1% of the institutions. In general, in 44% of the FIs the most students (80 to 100%) have access to the internet at least by cell phone, and that only a minority of them have access to activities exclusively by cell phone. We concluded that DE was few used in high school, and the teachers have few training for it before the current pandemic. With the suspension of face-to-face classes the FIs adopted the RE after teacher training. There is still information about the success of these educational modalities, causing doubts about the future use in high school, but it is known that more knowledge is needed in the area.